Cellular hierarchies predict drug response in acute myeloid leukemia - Raffel, Simon; Velten, Lars; Haas, Simon (Cancer cell, 2022)
In a recent Nature Medicine study, Zeng and colleagues integrate both genomic and stem cell models of acute myeloid leukemia (AML) by deconvoluting cellular hierarchies of more than 1,000 AML samples. This work introduces a framework capable of predicting drug responses to targeted therapies in future clinical trials.